2011
DOI: 10.1007/s00227-011-1849-6
|View full text |Cite
|
Sign up to set email alerts
|

Sediment tolerance of Sargassum algae inhabiting sediment-covered rocky reefs

Abstract: Although sediment deposition has detrimental effects on macroalgal settlement and recruitment, fucoid algae (mainly Sargassum duplicatum) thrive on rocky reefs always overlaid with fine sediments in sheltered sites of Kagoshima, Japan. The aim of the present study was to assess their ability to settle and recruit onto sedimentcovered substrata. A transplant experiment using boulders with Sargassum juveniles attached showed that the 30-day survival rate was as high as 50% even for the juvenile stage (\10 mm) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, it is difficult to judge the relative role of these factors without known environmental tolerances of Sargassum populations to these variables. We suggest further investigation into the specific thresholds of tropical Sargassum populations to these and other factors, such as sediment load (Kawamata et al 2012), to clarify their relative role and seasonal importance in future quantitative models.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to judge the relative role of these factors without known environmental tolerances of Sargassum populations to these variables. We suggest further investigation into the specific thresholds of tropical Sargassum populations to these and other factors, such as sediment load (Kawamata et al 2012), to clarify their relative role and seasonal importance in future quantitative models.…”
Section: Discussionmentioning
confidence: 99%
“…may have been more abundant at sandy sites due to greater tolerance to sedimentation than Sargassum spp. [61] , [62] , although some species of Sargassum are capable of recruiting to cobbles covered with fine sediment [63] . Macroalgae that are able to trap and bind sediments can benefit from sedimentation [55] , [58] .…”
Section: Discussionmentioning
confidence: 99%
“…Further, these effects appear to be context dependent, as one study showed sediments provided nutrient benefits (Schaffelke 1999), while another demonstrated negative impacts across demographic parameters (Umar et al 1998). On temperate reefs, where the consequences of sediment loads for macroalgae are better studied, the effects on growth are primarily negative (e.g., Kawamata et al 2012) by blocking light and gas or nutrient exchange (reviewed by Airoldi 2003; but see Kawamata et al 2011). Yet one study (Gorgula and Connell 2004) showed that nutrient enrichment in the sediments increased algal turf cover.…”
Section: Introductionmentioning
confidence: 99%